Al-Ghazâlî’s Concept of Causality and Quantum Physics: Finding a Point of Relevance - Hasan Al-Asy'ari; Yongki Sutoyo; Aldy Pradhana (TSAQAFAH, 2022)
Al-Ghazâlî views the connection between what is believed to be natural cause and effect is not necessary. For him, God is the Agent in every event. He is the determining factor. As a result, a natural event cannot be seen with certainty, in other words it is probabilistic. On the other hand, quantum physics developed in the early 20th century, which tries to explain the microscopic world is only able to predict events probabilistically. So it can be said that quantum physics that emerged at the beginning of the 20th century supports and affirms the views of al-Ghazâlî formulated in the 11th century at least in terms of probability. In addition, the many strange and complicated things that have not been well explained in the atomic world should be an indication that a more in-depth and thorough study of the universe leads to an increasingly "visible" Entity that is Almighty, namely God—where He has made nature as the âyât (signs) of His existence. Furthermore, from this study of al-Ghazâlî’s concept of causality and quantum physics, it can be understood that there are differences that become the end of the problem, namely metaphysical beliefs. So that an important effort that must be made to build Islamic science is to form an intellectual commitment based on metaphysical beliefs originating from Revelation.